تسامُح الإسلام في العهدة العمرية: دراسة تحليلية Tolerance of Islam in Umar Assurance: An Analytical Study - Muhammad Amin Said, Zana; Mustapha, Maziah (IIUM, 2017)
This research attempts to elucidate the subject of tolerance of Islam with Christians of Jerusalem during the caliphate of Umar bin al-Khaṭṭāb in the light of his treaty, which is known as “Umar's Assurance to the People of “Aelia” (al-'Uhdah al-Umariyyah). This treaty expounds the rights and duties of Christians and Islamic tolerance towards them. The researcher adopts historical and inductive methods for the transmission of original texts of al-'Uhdah al-Umariyyah and elaboration of it in the light of the Quran, Ḥadith and historical facts. Likewise, the analytical method is employed for discoursing on texts and deliberating on relevant historical events. Furthermore, it distinguishes those articles of al-'Uhdah al-Umariyyah which are eligible for inference from that which are ineligible followed by discussion of differed opinions and preference of preponderant one from them conforming to the authentic maxims and rulings. This research is concluded with several significant findings and one of them is that this treaty guaranteed the preservation of personal rights of Christians of Jerusalem such as protection of their body and property, and their religious privileges. This treaty assures that they should not be forcibly converted to Islam but their churches should be protected. Moreover, it guarantees their financial rights in terms of ownership of property and its collection. This research is deemed particularly significant because it establishes the tolerance of Islam with Christians during the period of second Caliph, which is conducive to remove the misconceptions based on unproven facts among Muslims about how Caliph treated non-Muslim citizens of Islamic state.